Treatment of COVID-19 in Patients With Sarcoidosis - Kondle, Shreya; Hou, Titus; Manansala, Michael; Ascoli, Christian; Novak, Richard M.; Sweiss, Nadera (Frontiers in Medicine, 2021)
Recent case reports and studies on treating COVID-19 in patients with chronic sarcoidosis describe different treatment modalities ranging from glucocorticoids to biologic medications. This review article summarizes 7 case series and reports totaling 46 patients. While one case report suggested that sarcoidosis medications such as glucocorticoids may lengthen the COVID-19 disease course, another study with a larger registry suggests they do not. More studies are needed to elucidate an improvement in outcomes. It is possible that addition of TNF-alpha inhibitors at COVID-19 diagnosis decreases hospitalization rate. Overall, it is difficult to make firm conclusions regarding treatment given the heterogeneity of treatment modalities in the current literature. Our summarized findings are outlined with the opinions of sarcoidosis, pulmonary, and infectious disease experts in a flow chart that provides clinicians with our proposed management algorithm for sarcoidosis patients who develop COVID-19. We emphasize a need for exchange of information regarding management of COVID-19 in the setting of sarcoidosis to further improve treatment in this vulnerable population of patients.